2007
DOI: 10.1055/s-2006-956777
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cervical Remodeling during Pregnancy and Parturition: Mechanisms and Current Concepts

Abstract: The cervix serves as a protective barrier from invading microorganisms and as a structural barrier to delivery of the fetus. Among all biological processes, the phenomenal connective tissue remodeling that occurs in the cervix during and after parturition is unparalleled in scope and magnitude. The process of connective tissue remodeling in the cervix during pregnancy occurs in four stages: softening, ripening, dilation, and repair. Although overlapping in time, each stage is uniquely regulated. Results from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
293
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(308 citation statements)
references
References 98 publications
7
293
1
7
Order By: Relevance
“…Uterine cervical epithelial cells are now believed to play a central role in uterine CR by regulating multiple functions, cited earlier in the introduction (Barclay et al 1993, Pfundt et al 1996, Mahendroo et al 1999, Minjarez et al 2000, Word et al 2007. We have previously shown that exogenous VEGF administered to ovariectomized mice induces folding of the uterine cervical epithelia layer using SEM and interpreted these data to mean that VEGF induces proliferation of uterine cervical epithelial cells ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Uterine cervical epithelial cells are now believed to play a central role in uterine CR by regulating multiple functions, cited earlier in the introduction (Barclay et al 1993, Pfundt et al 1996, Mahendroo et al 1999, Minjarez et al 2000, Word et al 2007. We have previously shown that exogenous VEGF administered to ovariectomized mice induces folding of the uterine cervical epithelia layer using SEM and interpreted these data to mean that VEGF induces proliferation of uterine cervical epithelial cells ).…”
Section: Discussionmentioning
confidence: 78%
“…A detailed understanding of uterine cervical epithelial biology has become essential because it is now believed that they play important and broad range of roles during uterine cervical remodeling (CR), which include i) maintaining fluid balance via synthesis of hydrophilic hyaluronan, glycosaminoglycan, and aquaporins; ii) proliferation and differentiation; iii) regulation of paracellular transport of solutes via tight junctions; iv) providing a protective barrier against invading microorganisms, and mediating inflammatory and adaptive immune responses; and v) acting as an 'endocrine' gland by synthesizing prostaglandins, chemokines, and cytokines (e.g. interleukin-8) and steroid hormones (Barclay et al 1993, Pfundt et al 1996, Mahendroo et al 1999, Minjarez et al 2000, Word et al 2007. It is likely, as some studies suggest that uterine cervical epithelial cells may play the central role in CR.…”
Section: Introductionmentioning
confidence: 99%
“…17;23 -25 It has been proposed that cervical changes during pregnancy occur in four phases: softening, ripening, dilation, and changes which occur after parturition. 26 We present a unique report of the signaling and metabolic pathways involved in phase four of this process: cervical dilation and remodeling after term labor. In the current study, 52 pathways documented by the Metacore™ database were noted to be significant.…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…The cervix is extensively remodeled throughout gestation in order to open sufficiently for safe passage of the fetus during childbirth. Cervical remodeling during pregnancy and parturition is a single continuous process that can be loosely divided into four overlapping phases termed softening (phase 1), ripening (phase 2), dilation/labor (phase 3), and post partum repair (phase 4; Liggins 1978, Word et al 2007.…”
Section: Introductionmentioning
confidence: 99%